A Lacustrine Biomarker Record From Rebun Island Reveals a Warm Summer Climate in Northern Japan During the Early Middle Holocene Due to a Stronger North Pacific High - Yamamoto, Masanobu; Wang, Fangxian; Irino, Tomohisa; Suzuki, Kenta; Yamada, Kazuyoshi; Haraguchi, Tsuyoshi; Gotanda, Katsuya; Yonenobu, Hitoshi; Chen, Xuan-Yu; Tarasov, Pavel (Frontiers in Earth Science, 2021)
The summer climate of northern Japan since the last glacial period has likely been determined by atmospheric and oceanic dynamics, such as changes in the North Pacific High, the position of the westerlies, the Kuroshio Current, the Tsushima Warm Current (TWC), and the East Asian summer monsoon. However, it is unclear which factor has been most important. In this study, we analyzed leaf wax δ13C and δD and glycerol dialkyl glycerol tetraethers (GDGTs) in sediments from Lake Kushu, Rebun Island, northern Japan, and discuss changes in climate over the past 17,000 years. The GDGT-based temperature, the averaged chain length, δ13C and δD of long-chain n-fatty acids indicated that the climate was cold during the Oldest Dryas period ~16 ka and warm in the early Middle Holocene from ~9 to 6 ka. This climate change is consistent with the sea surface temperature in the Kuroshio–Oyashio transition, but inconsistent with changes in the TWC in the Sea of Japan. The results imply that the summer climate of northern Japan was controlled mainly by changes in the development of the North Pacific High via changes in the position of the westerly jet and East Asian summer monsoon rainfall, whereas the influence of the TWC was limited over a millennial timescale.